Chemical priming enhances plant tolerance to salt stress - Zulfiqar, Faisal; Nafees, Muhammad; Chen, Jianjun; Darras, Anastasios; Ferrante, Antonio; Hancock, John T.; Ashraf, Muhammad; Zaid, Abbu; Latif, Nadeem; Corpas, Francisco J.; Altaf, Muhammad Ahsan; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Salt stress severely limits productivity of crop plants worldwide and its detrimental effects are aggravated by climate change. Due to a significant world population growth, agriculture has expanded to marginal and salinized regions, which usually render low crop yield. In this context, finding methods and strategies to improve plant tolerance against salt stress is of utmost importance to fulfill food security challenges under the scenario of the ever-increasing human population. Plant priming, at different stages of plant development, such as seed or, seedling, has gained significant attention for its marked implication in crop salt stress management. It is a promising field relying on applications of specific chemical agents which could effectively improve plant salt stress tolerance. Currently, a variety of chemicals, both inorganic and organic, which can efficiently promote plant growth and crop yield are available in the market. This review summarizes our current knowledge on the promising roles of diverse molecules/compounds, such as hydrogen sulfide (H2S), molecular hydrogen, nitric oxide (NO), hydrogen peroxide (H2O2), melatonin, chitosan, silicon, ascorbic acid (AsA), tocopherols and trehalose (Tre), as potential primers that enhance salinity tolerance of crop plants.